2016
DOI: 10.1115/1.4034416
|View full text |Cite
|
Sign up to set email alerts
|

Modulation and Radial Migration of Turbine Hub Cavity Modes by the Rim Seal Purge Flow

Abstract: In the present paper, the results of an experimental and numerical investigation of the hub cavity modes and their migration into the main annulus flow are presented. A one-and-a-half stage, unshrouded and highly loaded axial turbine configuration with three-dimensionally shaped blades and cylindrical end walls has been tested in an axial turbine facility. Both the blade design and the rim seal purge flow path are representative to modern high-pressure gas turbines. The unsteady flow field at the hub cavity ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Schädler et al [35] reported unsteady flow measurements in a stage and a half turbine with a more geometrically complex axial rim seal than those considered by Cao et al and Jakoby et al "Hub cavity modes" in the frequency range ~7Ω to 19Ω were detected and found to propagate up to 30% of span in the main flow annulus. These modes were suppressed at higher purge flow rates and their effect on aerodynamic pressure losses was highlighted, lessening the expected reduction in losses as purge flow rate was reduced.…”
Section: Jakoby Et Al'smentioning
confidence: 98%
See 3 more Smart Citations
“…Schädler et al [35] reported unsteady flow measurements in a stage and a half turbine with a more geometrically complex axial rim seal than those considered by Cao et al and Jakoby et al "Hub cavity modes" in the frequency range ~7Ω to 19Ω were detected and found to propagate up to 30% of span in the main flow annulus. These modes were suppressed at higher purge flow rates and their effect on aerodynamic pressure losses was highlighted, lessening the expected reduction in losses as purge flow rate was reduced.…”
Section: Jakoby Et Al'smentioning
confidence: 98%
“…[33], Savov et al [34], Schädler et al [35], Jakoby et al [24] and Town et.al. [36] have all indicated unsteady rim seal cavity flow features which are unrelated to blade passing.…”
Section: Experimental Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Khilnani and Bhavnani 21 revealed sealing characteristics of a typical rotor-stator cavity mainstream flow experimentally. Schädler 22 conducted an experimental and numerical investigation for the cavity leakage flow that migrating into the main annulus flow. A hub cavity mode that weakens the benefit in loss reduction was also proposed.…”
Section: Introductionmentioning
confidence: 99%